2023
DOI: 10.1007/s12020-023-03588-0
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and neonatal outcomes of twin pregnancies complicated by gestational diabetes mellitus

Zhengyu Zhang,
Lingwei Mei,
Li Li
et al.

Abstract: Introduction Gestational diabetes mellitus (GDM) is associated with a higher risk of adverse maternal outcomes, but its effects on maternal and perinatal outcomes of twin pregnancies remain conflicting. Methods This retrospective cohort study included all primipara who delivered twin pregnancies at a single tertiary perinatal center between January 1, 2016 and December 31, 2022. Excluded were those who had a single pregnancy, twin pregnancies with pre-exis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 39 publications
2
0
0
Order By: Relevance
“…Our study found significant variations in maternal complications across the groups, with Group A (Pre-Gestational Diabetic) experiencing the highest rate of complications (47%), followed by Group B (Gestational Diabetic) at 25%, and Group C (Control) at 12%. This trend is consistent with the literature, which indicates that gestational diabetes mellitus (GDM) is associated with a higher risk of adverse maternal outcomes 17 . The elevated risk in pre-gestational diabetic patients underscores the need for heightened surveillance and management in this group.…”
Section: Discussionsupporting
confidence: 93%
“…Our study found significant variations in maternal complications across the groups, with Group A (Pre-Gestational Diabetic) experiencing the highest rate of complications (47%), followed by Group B (Gestational Diabetic) at 25%, and Group C (Control) at 12%. This trend is consistent with the literature, which indicates that gestational diabetes mellitus (GDM) is associated with a higher risk of adverse maternal outcomes 17 . The elevated risk in pre-gestational diabetic patients underscores the need for heightened surveillance and management in this group.…”
Section: Discussionsupporting
confidence: 93%
“…Our study found significant variations in maternal complications across the groups, with Group A (Pre-Gestational Diabetic) experiencing the highest rate of complications (47%), followed by Group B (Gestational Diabetic) at 25%, and Group C (Control) at 12%. This trend is consistent with the literature, which indicates that gestational diabetes mellitus (GDM) is associated with a higher risk of adverse maternal outcomes 17 . The elevated risk in pre-gestational diabetic patients underscores the need for heightened surveillance and management in this group.…”
Section: Discussionsupporting
confidence: 93%